A bifunctional MXene-modified scaffold for photothermal therapy and maxillofacial tissue regeneration. Issue 6 (16th November 2021) - Li, Fengji; Yan, Yanling; Wang, Yanan; Fan, Yaru; Zou, Huiru; Liu, Han; Luo, Rui; Li, Ruixin; Liu, Hao
Abstract: Oral squamous cell carcinoma is one of the most common malignant tumours in the oral and maxillofacial regions and is highly malignant and prone to recur despite the development of various effective treatments, including surgery and chemoradiotherapy. Actually, it is difficult to ensure the complete elimination of tumour cells, and maxillofacial bone defects caused by surgery are hard to heal by themselves. In addition, chemoradiotherapy can bring serious side-effects. Therefore, it is imperative to develop a postoperative therapy to kill residual squamous cancer cells and repair bone defects without any side-effects. Here, we prepared a 3D scaffold by a 3D printing technique and freeze-drying method, which contained collagen, silk and hydroxyapatite (CSH) and was functionalized with MXene nanosheets (M-CSH). The considerable photothermal effect with long-term stability can significantly kill squamous CAL-27 cancer cells in vitro and inhibit tumour growth in vivo, increasing the probability of the M-CSH scaffold being applied in the photothermal therapy of oral squamous cell carcinoma. Moreover, the cell proliferation- and osteogenic-related protein expression of mouse embryonic osteogenic precursors (MC3T3-E1) indicated excellent biocompatibility and osteogenic activity of M-CSH scaffolds. The good compression modulus (52.83 ± 2.25 kPa) and in vivo bone formation performance made it possible to be used as reconstructive materials for bone defects. This scaffold is likely promising in future tissue engineering, especially for the multifunctional treatment of maxillofacial tumours.